STUDI TENTANG PENGARUH SUBSTITUSI TEPUNG TERIGU DENGAN TEPUNG TEMPE TERHADAP KARAKTERISTIK ROTI YANG DIHASILKAN - Rizwana Wahyuni, Rizah; Wisaniyasa, Ni Wayan (Agrotekno; Vol. 14, No. 1 Februari 2008, 2012)
This research was aimed to study the effect of using the tempe flour to substitute the wheat flour on the characteristic of breads produced, as well as to know how much the tempe flour can be used to substitute wheat flour in order to breads that could still be accepted by panelist with the best characteristic. This research was design using Randomized Block Design with 6 level substitutions treatments, namely: 100% wheat flour : 0% tempe flour, 98% wheat flour : 2% tempe flour, 96% wheat flour : 4% tempe flour, 94% wheat flour: 6% tempe flour, 92% wheat flour : 8% tempe flour, 90% wheat flour : 10% tempe flour. There were three replications of each treatments, so that be 18 experiments unit. The data was analyzed with ANOVA and followed by Duncan’s Method if the treatments effected the parameter. The research showed that substitution treatment up to 96g wheat flour: 4g tempe flour has result breads with the best characteristic in which leavening bread loaves was 404,83%, water content was 36,62(%w/w), ash content was 0,72(%w/w), and protein content was 9,31(%w/w). According to sensory analyzed of the breads produced, the colour of breads were yellow-brown, flavor were neutral, like of taste, texture were moderately soft, sponge formation were moderately variant, and overall acceptance were like.
Keywords: tempe flour, substitutions, characteristic, breads